Two new cave-dwelling species of Bent-toed Geckos from Saraburi and Loei provinces, Thailand (Squamata: Gekkonidae: Cyrtodactylus) - Sumontha, Montri; Panitvong, Nonn; Kunya, Kirati; Donbundit, Nattasuda; Suthanthangjai, Winai; Suthanthangjai, Maneerat; Phanamphon, Eakarit; Pauwels, Olivier S. G. (Zootaxa, 2024)
We describe Cyrtodactylus meesookae sp. nov. from a cave on Khao Nam Phu (14°34’33.2”N, 101°08’42.6”E), a limestone hill in Saraburi Province, central Thailand, and C. wiboonatthapoli sp. nov. (previously confused with C. papilionoides) from a cave on Phu Pha Sana (17°10’33.8”N 101°57’52.5”E), a limestone hill in Loei Province, northeastern Thailand. These two micro-endemic, trogloxene species, separated by a distance of about 300 airline km, share a typical habitus for limestone-dwelling species and a relatively similar dorsal pattern, but they are readily distinguished by scalation characters.